Development of secure Internet of Vehicle Things (IoVT) for smart transportation system - Karim, Ahmad (Computers & electrical engineering, 2022)
Intelligent Transportation Systems (ITS) have attracted significant attention for their potential to improve transportation in urban and highway contexts as automotive infrastructures and automobiles have progressed. The characteristics of heterogeneity, constrained resources, scaling requirements, an uncontrolled environment, and so on make security and privacy concerns far more difficult to tackle than they are today. The high availability required by IoT networks may risk the integrity and security of data carried over the network. Because the majority of security threats occur during data routing activities, developing a safe routing protocol for IoT networks has emerged as the most important research subject. The efficient procedures required to allow secure data transfer for autos enabled by IoT technology are detailed here. Using a novel cryptography-based routing mechanism, this study demonstrates how to protect V2V and V2I communications in the context of the VANET against a wide range of cyber threats. It is a data encryption and decryption technology based on attributes and identity that has been designed to have the lowest computational overhead while retaining the best level of security. To provide efficient message authentication and integrity while ensuring vehicle privacy and safeguarding vehicular communications, a hybrid cryptography system integrating ABS and IBS, named AIBS (Attribute-Identity Based Signature), was created. The recommended cryptography-based solution is tested in the presence of prospective attackers on the network while using the NS2 tool. The simulation results have been measured in terms of average throughput, Packet Delivery Ratio (PDR), communication delay, and communication overhead.